Konsep Syariah Dan Sejarah Intelektual Pemikiran Inflasi : Telaah Kritis Atas Gagasan Al Maqrizi dan relevansinya Terhadap Kondisi Inflasi di Sumatera Utara - Putra, Muhammad Umar Maya; Akmal Tarigan, Azhari; Ridwan, M (JURNAL SYIAR-SYIAR, 2025)
The study of inflation from the perspective of Islamic economics has been present since the classical era, with Al-Maqrizi (1364–1442 CE) emerging as one of the most influential figures in developing early Islamic economic theories. As a prominent historian and economist during the Mamluk dynasty in Egypt, Al-Maqrizi's thoughts remain highly relevant due to his firsthand observations of the economic crisis in 15th-century Egypt. This research employs a qualitative historical approach by examining classical and contemporary literature, including Al-Maqrizi’s seminal work Ighatsah al-Ummah bi Kashf al-Ghummah, and integrates it with a quantitative analysis of inflation data in North Sumatra and Indonesia from 2015 to 2020. Al-Maqrizi categorized inflation into two types: natural inflation, caused by uncontrollable natural factors such as disasters, and man-made inflation, stemming from corruption, poor fiscal policy, and excessive use of copper currency (fulus). His thoughts represent a critical response to the economic, political, and moral degradation of his time, emphasizing the importance of maintaining currency standards, fair wealth distribution, and moral integrity in leadership.The analysis of inflation data in North Sumatra reveals dynamics consistent with Al-Maqrizi's theory, particularly regarding the peak inflation rate of 6.34% in 2016, which later declined to 1.96% in 2020. Compared to the national average, North Sumatra experienced relatively higher inflation, indicating structural imbalances and governance challenges. This study shows that Al-Maqrizi’s thoughts offer a holistic Islamic economic framework that integrates economics, fiqh, and ethics. His ideas remain applicable today, particularly in promoting justice, transparency, and responsibility in economic policy. By combining historical-intellectual analysis and empirical data, this research provides a comprehensive understanding of how Islamic economic principles can guide contemporary inflation control and sustainable economic development